NILAI-NILAI SOSIAL DALAM PUISI SUJUD KARYA GUS MUS - Muhammad Heru Adriansyah; Holila, Zenita Cilvia; Julianto, Indra Rasyid (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2024)
This research focuses on examining the social values ​​in the poem Sujud by K.H. Ahmad Mustofa Bisri, or Gus Mus. In the poetry anthology Negri Meat, this research aims to describe the forms of social values ​​in Sujud poetry. The data collection method in this research uses descriptive qualitative using a sociological approach, especially in the social value aspect. The aim of the qualitative descriptive approach is to obtain information about the appropriate social values ​​in Sujud poetry. In this research, data analysis is used as a content analysis method. Data collection techniques were analyzed using heuristic and hermeneutic analysis. In the analysis of this study, results can be drawn from social values, responsibility, concern, religion, protest and justice. Meanwhile, the form of political values ​​is about struggle, persuasion, protest and struggle.